(untitled) (AL MUNAZHZHARAH, 2021)
The fulfillment of a living during the COVID-19 pandemic carried out by traders in Trenggalek District, Trenggalek Regency has decreased. This is due to income due to the covid-19 pandemic, although wives can understand the conditions experienced by their husbands. This study answers three problem formulations: 1. living from the perspective of Islamic law, 2. How does the husband make a living, 3. How to fulfill the Covid-19 pandemic and his livelihood towards family harmony. The results of this study indicate that of the five family couples, that of the 5 family couples stated that the covid-19 pandemic greatly affected the income and income that must be given to husband and wife to meet their daily needs. reduced, it did not affect the harmony of the traders in Trenggalek. Because the family benchmark is not always measured by material.